Antibiotic susceptibility pattern, pigment production and molecular characterisation of Pseudomonas aeruginosa isolates from clinical and soil sources - Safren, Siti Rukhaiyah (2015)
Pseudomonas aeruginosa (P. aeruginosa) is increasingly recognized as an emerging opportunistic pathogen of clinical relevance (Van Eldere, 2003) and well known for its adverse effects in the clinical setting. However, its adverse effects from the environmental source are still not much explored in comparison to those of clinical origin. This scope of research is also lacking in Malaysia, as there is the possibility of the environmental to be the initial source of infection. This study was conducted to isolate and analyse the difference of pigmentation production, antibiotic susceptibility patterns, virulence-related genes (exoU, exoS, LasB, PlcH, AlgD and Nan1) among 50 P. aeruginosa from diverse local clinical isolates (n = 30) obtained from a main Malaysian hospital and soil isolates (n =20) from random locations of Selangor state. P. aeruginosa isolates were further characterised for their DNA fingerprints using ERIC-PCR and BOXPCR analysis. Only positive culture results for P. aeruginosa were included in this study. P. aeruginosa ATCC 27853 strain was also included as a reference strain (n = 51). Identification was done by conventional (different inducing media, selective media and differential media, gram staining, biochemical tests and antibiotic susceptibility test) and molecular approaches (PCR 16s rRNA P. aeruginosa specific primer, PCR virulence-related genes, ERIC-PCR and BOXPCR). Based on the results obtained in this study, it showed that pyocyanin pigment were more common in the clinical isolates compared to soil isolates, and was known to contribute to resistance ability toward antibiotics. Pyocyanin pigment has been resolved to show cytotoxic properties and consequently help the multidrug resistance capability in clinical settings. Besides, it showed that high rate of antibiotic susceptible among 50 P. aeruginosa isolates from diverse local clinical and soil sources against antibiotic agents used, were in contrast with previous studies that showed high rate of antibiotic resistant in P. aeruginosa spp. Less than 30% of P. aeruginosa isolates from clinical sources were MDR compared to none from soil sources. Moreover, it indicated that the clinical isolates possess slightly higher virulence-associated genes compared to the soil isolates. exoS, lasB and algD genes grant high percentage of presence in both the soil and clinical isolates, meanwhile nan1 gene grant the lowest percentage of presence in both the soil and clinical isolates. While only the clinical isolates grant high percentage of plcH gene possession, it contrasted to the soil isolates that grant low percentage of the same gene. In detailing with mutual relationship for genes (exos andexoU),the results showed that the soil isolates grant higher percentage of both exoU and exoSgenes (EXOS+ EXOU+ or EXOS- EXOU-) compared to the clinical isolates. In contrast, result with the clinical isolates grant a higher percentage of inverse relationship for both genes (exos and exoU) whereby one isolate that carried exoU does not carry exoS and vice versa (EXOS+ EXOU- or EXOS- EXOU+), but not both. In fact, this study also indicated that MDR isolates of P. aeruginosa from the clinical isolates have high possibility of exoU gene possession compared to other virulence-associated genes. By using genotypic approaches (BOX-PCR and ERIC-PCR), it showed comparison between the soil (environmental) and clinical isolates under BOX and ERIC DNA profiles. From the discriminatory indexes calculation in this study, it showed that the composite of BOX ERIC dendrogram highly discriminate P. aeruginosa isolates from the soil and clinical, and also ERIC dendrogram provides a more specific analysis in terms of distinctive clusters, which referred to the meaningful clusters based on pigmentation, antibiotic susceptibility and virulence-associated genes profiling results that were useful in clustering the heterogeneous group of P. aeruginosa isolates. Using both molecular approaches, all the 51 P. aeruginosa isolates from the soil and clinical sources (including positive control, P. aeruginosa ATCC 27853, clinical isolate) were able to be differentiated and it indicated diverse isolates. Besides, both methods are satisfactory for genetic analysis of local soil and clinical P. aeruginosa isolates. From testing both the molecular methods and based on the discriminatory index value, it showed that using only ERIC-PCR method is sufficient to discriminate and analyze local soil and clinical P. aeruginosa isolates, whereby this approach is more effective because low cost, shorter duration and less effort allocated.